THERMODYNAMIC AND KINETIC STUDIES FOR THE BINDING OF LEAD ION BY CHELATING WITH THEOPHYLLINE 1,3-DIMETHYLXANTHINE (THERAPY DRUG) - HUDA N AL-ANI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Chelating therapy is a medical procedure that involves the administration of chelating agents to remove heavy metals from the body; chelating agents detoxify heavy metals and toxins, converting them to inactive forms which were excreted out from the body. This work demonstrates the complication of the drug with toxic heavy metal lead (Π) ion. Methods: All the experiments were performed at different temperature (303, 308, 313, 318, and 323) °K, by spectrophotometric method. The electronic spectra of the mixture of drug and lead ion show a bathochromic (red) shift in ʎmax, the absorbance change caused by a complex arrangement between the lead ion and drug. Results: The stoichiometry of the complex formed was calculated using continuous variation method, it was found (1:2) that the durability constant was estimated that the standard thermodynamic parameters ΔH°, ΔG°, and ΔS° were determined, the negative values of free energy changes ΔG° indicate a spontaneous complexation process. The positive values of enthalpy change indicate an endothermic process with an increase in entropy change ΔS° (positive), that means the process in an entropy driven. Conclusion: The kinetic studies of the complexation of drug and ion were found to follow the second-order reaction, which was confined by the straight line and a high rate constant.